The Principal's Strategy in Improving the Quality of Teacher Competence at Senior High School: Strategi Kepala Sekolah Dalam Meningkatkan Kualitas Kompetensi Guru di SMA - Mashudi Harianto; Isa Anshori (Academia Open, 2022)
The purpose of this study was to explore the competence and understand the principal's strategy in improving the quality of teacher competence at SMA Islam As Sakinah Sidoarjo, the obstacles faced by the principal in improving the quality of teachers, as well as the principal's strategy in overcoming the obstacles which appear in efforts to improve the quality of teachers at SMA Islam As Sakinah Sidoarjo. This study uses a qualitative method with a phenomenological approach. The research subjects were determined purposively, they are the principal and teachers of SMA Islam As Sakinah Sidoarjo. Observation, interview and documentation are data collection techniques. Reduction data, display data, and conclusion are the steps of data analysis. To check the validity of the data using source triangulation and discussion with the supervising lecturer. The results of the study prove that the principal's strategies in improving the quality of teacher competence at SMA Islam As Sakinah Sidoarjo are: (1) further study of the S.2 professional degree, (2) activating teachers in increasing competence, (3) providing motivation, (4) maximizing the function of the school library, (5) conducting periodic supervision and (6) providing welfare benefits. The obstacles faced by principals in implementing strategies to improve the quality of teacher competence at SMA Islam As Sakinah Sidoarjo are the lack of interest and awareness of teachers, insight into thinking which still tends to be exclusive, lack of teacher supervision activities and several other external factors. While the solutions to overcome the obstacles which appear include providing motivation and good treatment, involving teachers in scientific activities and increasing the implementation of teacher supervision.